2019
DOI: 10.1111/srt.12716
|View full text |Cite
|
Sign up to set email alerts
|

Plasma radiofrequency ablation for treatment of benign skin lesions: Clinical and reflectance confocal microscopy outcomes

Abstract: Background:In the latest few years, plasma radiofrequency ablation has turned out a good option for treatment of several benign skin lesions. The technique can be easily performed to treat skin lesions with limited tissue invasion and no residual scars or hypo/hyperpigmentation areas.Objective: The aim of this study was to assess the effects of plasma radiofrequency ablation in treatment of benign skin lesions, through clinical and reflectance confocal microscopy outcomes.Methods: Six patients who presented be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Recently, plasma radiofrequency ablation has been used to remove various nevi in different parts of the body such as skin and around the eye and its safety has been discovered (33,34). Based on our previous studies on the PANIS method and its e cacy, it has shown that this method can be a minimally invasive technique for various ocular surface disorders (10)(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, plasma radiofrequency ablation has been used to remove various nevi in different parts of the body such as skin and around the eye and its safety has been discovered (33,34). Based on our previous studies on the PANIS method and its e cacy, it has shown that this method can be a minimally invasive technique for various ocular surface disorders (10)(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma blepharoplasty is a safe and effective procedure with an overall high patient satisfaction rate. The advantages of the technique are the high precision, short operation time, no bleeding, less damage to other tissues, rapid formation of postoperative protection layer, fast healing of wound surface, immediate return to normal activity, no visible scars, no hyperpigmentation, no infection, no pain, and very slight inflammatory reaction after sessions …”
Section: Discussionmentioning
confidence: 99%
“…Its applications are many, ranging from the removal of unsightly skin lesions, such as fibromas and dermal nevi (Figure 1A,B), xanthelasma palpebrarum 7 (Figure 2A,B), dyskeratosis and angiomas (Figure 3A,B), warts (Figure 4A,B), solar lentigo (Figure 5A,B), and seborrheic keratosis 6 (Figure 6A,B), to the correction of scars, 4,8 and treatment of blepharochalasis 5 (non‐surgical blepharoplasty) (Figure 7A,B) (Figure 8A,B), periocular and perioral wrinkles, 9 and active acne 9,10 (the PRF ablation tool used in the cases shown in the photos is DAS Medical—Technolux).…”
Section: Figurementioning
confidence: 99%
“…Recently, PRF ablation has shown to be very useful for facial skin esthetic treatments 4 . The technique has many advantages, among which are its high precision, no risk of scarring, hyperpigmentation and infection, and a slight tendency for tenderness 6 . Furthermore, the short operation time, lack of risk of bleeding, low chance of damage to other tissues, rapid formation of a postoperative protection layer, fast healing of the wound surface, a very low incidence of inflammatory reactions after sessions, and fast recovery leading to an immediate return to normal activity satisfy the requests of the most demanding patients 2,3 .…”
Section: Figurementioning
confidence: 99%